Efecto de la intervención educativa de enfermería sobre prevención de infecciones por catéter permanente en pacientes de hemodiálisis Del Hospital Regional De Loreto, Punchana 2022 - Sandoval Reátegui, Delicia Isabel (2024)
The objective of the research was to determine the effect of the nursing educational intervention on the prevention of indwelling catheter infections in hemodialysis patients at the Loreto Regional Hospital, Punchana 2022. The quantitative method, pre-experimental design, in a time series with a single intervention group. The sample population was 27 patients. The instruments were used: questionnaire and observation sheet with a validity of 97.7% and 93.5%; and the reliability of 96.0% and 93.9% respectively. The educational program with a didactic structure was used; The Results were: before the intervention, 8 (29.6%) patients had adequate knowledge and 19 (70.4%) had inadequate knowledge; 3 (11.1%) presented adequate practice and 24 (88.9%) presented inadequate practice. For the effect of the educational intervention, Shapiro-Wilk normality tests, linear models, Mauchly sphericity and ANOVA analysis of variance were applied. Before and after 7 and 15 days post intervention the results were: 0.241; 0.063 and 0.053 in a normal distribution; The sphericity test obtained p>0.05 (p=0.209) and the analysis of variance (ANOVA) p=0.000 indicating a significant difference in knowledge about measures to prevent indwelling catheter infections. Before and after 7 and 15 days post intervention the results (0.135, 0.091 and 0.073) indicate a normal distribution, with the sphericity test p>0.05 was obtained (p=0.114), and the analysis of variance (ANOVA) p =0.000. The conclusion was that the educational intervention has a positive effect on the practice of measures to prevent indwelling catheter infections.